TO THE ISSUE OF DRILL STRING FAILURE PARAMETERS ESTIMATION DUE TO THE RESULTS OF CALCULATION AND EXPERIMENTAL STUDIES - Крижанівський, Євстахій Іванович; Витязь, Олег Юлійович; Грабовський, Роман Степанович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The estimation of the catastrophic failure of the metal of the long-term drill pipes operation was carried out. Determined were the conditions under which there were possible failures of the elements of the nipple and slleve sections of the drill pipes threaded connection З-133 on the first connected turn of the thread containing closed corrosion-fatigue crack with a depth (a/t)* . The interrelationship of criticals of the external transverse closed circular crack in the nipple section and the internal transverse closed circular crack in the sleeve section of threaded connection with the drill string weight was established.